PENGARUH ANTAR PERSPEKTIF NON KEUANGAN SERTA IMPLIKASINYA TERHADAP PERSPEKTIF KEUANGAN BERDASARKAN BALANCED SCORECARD - Sofia, Alfira; Stefani, Nicol (Program Studi Akuntansi FPEB UPI, 2015)
This study aims to determine the effect between non-financial perspective (learning and growth, internal business processes and customers) and its implications on financial perspective based on Balanced Scorecard at PT PLN (Persero) in 2002-2013.The method used in this research is descriptive and quantitative explanation. Sources of data in this study were obtained from secondary data. The secondary data consists of annual reports and statistical reports of PT PLN (Persero) obtained from the company website www.pln.co.id, as well as literature such as journals, previous research, and text book. This research uses Structural Equation Modeling - Partial Least Square (SEM-PLS) technique for multivariate analysis.In this research note that there is significant influence between non financial perspective at PT PLN (Persero) and there is significant influence from non-financial perspective to financial perspective.